Sibling influence on children's objectively measured physical activity: a meta-analysis and systematic review. Issue 1 (27th July 2018) - Kracht, Chelsea L; Sisson, Susan B
Abstract : Abstract: Children without siblings (only children) have higher rates of obesity than children with siblings. Childhood obesity may be prevented by minimising sedentary behaviour and accumulating sufficient physical activity in young children. A growing number of articles have examined the influence of siblings on physical activity and sedentary behaviour, yet these articles have not been synthesised. Objective: To synthesise literature and describe the influence of siblings on objectively measured physical activity and sedentary behaviour of children (ages 2–18 years). Design: Outcomes were analysed in a systematic review and meta-analysis. Data sources: PubMed, EMBASE, Web of Science and Medline OVID were searched for articles related to siblings, physical activity, sedentary behaviour and obesity outcomes from 1947 to March 2018. Eligibility criteria: Articles that evaluated sibling status on physical activity objectively measured by accelerometer or pedometer were included. Results: Nineteen articles, representing 17 independent datasets, were included in the review. Nine were included in the quantitative analysis. Pooled data from nine articles indicated children with siblings had higher moderate-to-vigorous physical activity (MVPA) relative to only children, with a potential dose response for higher number of children in household and higher MVPA (Mean Difference=3.13, 95% CI 1.90 to 4.35, p=0.001). Findings were mixed for the influence of siblings on sedentary behaviour and light physical activity. Summary/Conclusion: Children with siblings had healthier physical activity patterns, as measured by accelerometer or pedometer, than did only children. Suggested mechanisms include peer modelling, encouraging active transport and sports participation, opportunity for playmate and serving as additional caregivers. Trial registration number: CRD42017055463.